Redesigning the TIX ID Application Using the Design Thinking Method - Thoriq Farhan; Saifur Rohman Cholil (Communigate, 2025)
Technological advancements are continuously transforming the landscape of digital purchasing, particularly through smartphones, which enable various ordering activities, including online cinema ticket bookings. TIX ID serves as a platform that simplifies the process of purchasing cinema tickets from any location without the need to stand in line. Despite its advantages, users have raised concerns regarding the limited payment options, difficulties in cancelling ticket orders, lengthy account creation times, and challenges in submitting complaints. Therefore, it is essential for the TIX ID application to implement updates and modifications to enhance user convenience. Improving the User Interface (UI) and User Experience (UX) can effectively address these issues through the Design Thinking methodology. The Design Thinking approach prioritizes a user-centered perspective, positioning user satisfaction as a key solution to existing problems while fostering innovative ideas. The effectiveness of these enhancements will be evaluated using the Single Ease Question (SEQ), where a score of 6.4 out of 7 indicates that the redesigned User Experience meets user needs and provides the necessary features within the TIX ID application.